Analytical On-Load Subdomain Field Model of Permanent-Magnet Vernier Machines - Oner, Y.; Zhu, Z. Q.; Wu, L. J.; Ge, X.; Zhan, Hanlin; Chen, J. T. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
Permanent-magnet vernier machine (PMVM) is a relatively new type of PM machines. An analytical subdomain model accounting for tooth-tips and flux modulation poles is developed to accurately predict on-load field distributions in PMVMs. Based on two-dimensional (2-D) polar coordinate and magnetic vector potential, this method solves the Maxwell's equations in slot, air-gap, flux modulation pole slot (FMPS), and PM regions. Consequently, the electromagnetic performance such as cogging torque, back-electromotive force (EMF), electromagnetic torque, power factor, and magnet loss are calculated. In addition, the model can also be used for the evaluation of demagnetization withstand capability. The finite-element analysis (FEA) and experimental results validate the accuracy of the developed analytical model.
Keywords: Analytical calculation; cogging torque; finite-element analysis (FEA); load effect; permanent-magnet (PM); subdomain model; vernier machine; GENERAL FORMULATION; DESIGN; ROTOR; MOTOR; PM; HALBACH; Automation & Control Systems; Engineering; Instruments & Instrumentation